The effects of salinity and stocking density on the artificial incubation of the giant freshwater prawn, Macrobrachium rosenbergii (de man) eggs. - Ang, Kok Jee; Raffiq Ahmad, Kabir Ahmad; Cheah, S. H. (1987)
Two series of experiments were conducted to determine the optimum salinity and stockinq density for artificial incubation of the eggs of M. rosenbergii. Newly laid eggs and 9 day-old eggs of the prawn were stocked at a density of 500 eggs/litre and incubated at 0 p.p.t., 6 p.p.t. and 12 p.p.t. salinities respectively. The mean percentage of hatching after 18 days of incubation for the newly fertilized eggs were O%, 3±1%, 40±4% as compared to 2±1%, 23±2% and 65±3% for 9 day-old eggs at 0 p.p.t., 6 p.p.t. and 12 p.p.t. salinities respectively. In the stocking density experiments, newly laid eggs were stocked at the rate of 1000/1itre, 1500/1itre and 2000/1itre at 12 p.p.t. salinity and their mean percentage of hatchings were 37±1%, 33±3% and 16±3 respectively. The results from this indicate that the optimum salinity for hatching the eggs of the prawn artificially is 12 p.p.t. while the stocking density for the eggs is 1000 eggs/litre seems to be the most suitable.